APPLICATION OF 3D ELECTRICAL CAPACITANCE TOMOGRAPHY FOR PHASE FRACTION DETERMINATION AND STRUTURES IDENTIFICATION IN TWO-PHASE FLOWS - Banasiak, Robert; Wajman, Radosław; Fidos, Henryk; Fiderek, Paweł; Jaworski, Tomasz; Nowakowski, Jacek; Sankowski, Dominik (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2013)
In the industrial processes, where the direct monitoring is difficult, the application of the non-invasive electrical capacitance tomography system for the two-phase gas-liquid mixtures flow structures identification and the phase distribution calculation is of great importance. This paper presents the research results of development new non-invasive diagnostic methods. The new possibilities offered by the tomographic techniques applications for the purposes of the electrical quantities measurement, define today the standards of dynamic measurements. The proposed solution involves the possibility of applying the tomographic system to measure the fractions concentration distribution of the flow. The designed algorithms allowed the fast 3D visualization of the pipeline interior through the quick tomographic image reconstruction and their analysis and structure identification. The obtained diagnostic data could be useful in the context of monitor and control of the flow industrial facilities in the real time.